Adoção do CPC 47 e a qualidade da informação contábil sob a perspectiva do value relevance - Andrade, Juliana Carvalho (2021)
This research aimed to identify the association between the adoption of the new standard for revenue recognition - CPC 47 (Revenue from Contracts with Customers) and the relevance of accounting information. The study sample is composed of 216 non-financial publicly traded Brazilian companies listed on B3, in the period from 2016 to 2019, that is, two years before the new standard came into effect and two years later. 1.670 observations were analyzed and the adopted methodology was descriptive analysis and multiple linear regression. The results show that the adoption of CPC 47 is positively associated with the relevance of accounting information, also confirmed by the robustness test. In the sectoral analysis, it was observed that all sectors are associated, positively or negatively, with the price variable, with the exception of the Non-Cyclic Consumption (CNC) sector, that is, the adoption of CPC 47 influences the stock price. This research contributes to the literature on the value relevance of companies listed in B3 and to the assessment by interested agents, such as regulatory bodies, to monitor whether the adoption of regulations is contributing to the improvement of the quality of accounting information, from the point of view of investor.